Pengadaan dan Pemasangan Instalasi Listrik Lampu Taman di Perum Rajeg PSP RW02 Kecamatan Rajeg Kabupaten Tangerang - Suminto Suminto; Lili Solikhin; Anto Carmanto; Nurkahfi Irwansyah; Awaludin Saputra (Abdimisi, 2020)
In the world of education, every lecturer is required to do the Tri Dharma of higher education. One of the Tri Dharma of higher education is PKM (Community Service) activities. With this background, our lecturer and student team want to help the community. Perum PSP Rajeg is the northern part of Tangerang. In this housing, there is a garden area that is poorly maintained. Poorly maintained gardens are caused by poor lighting. The lighting is not good because there are no lights in the garden area. The dark area of the park causes people to dislike exercising in the park. If people do not like to exercise, the health level of the community is not optimal. If the community's health level is not optimal, it can easily be attacked by diseases. Because of this, our team of lecturers and students were moved to impose PKM on PSP Rajeg. The implementation of this community service activity is carried out by the method of conducting location surveys, discussing with the community about the needs they want to need. After conducting a location survey, it was found that the PSP Rajeg community needed lighting in the garden area. This is useful for community activities when exercising in the park. The installation of lights in the parking area is carried out between lecturers, students and community members. Installation of lights in the garden area is carried out with a total of 7 light points and poles, one light point uses a 25-watt energy-saving lamp. After carrying out this Community Service activity, the community members are happier to do sports in the parking area, so that the level of community health becomes better and is more resistant to various kinds of diseases that can attack. The community of PSP RW02 Rajeg, Rajeg sub-district, Tangerang district is very supportive and grateful for the implementation of this PKM activity.